Kontrak Jasa pada Perbankan Syariah : Wakalah, Kafalah dan Hawalah - Muhammad Arfan Harahap; Sri Sudiarti (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
Financial service activities provided by Islamic banking in Indonesia are applied with various service contracts such as wakalah, hawalah and kafalah. In its current operation, the service contract is still an issue that is discussed, especially regarding the conformity of the contract to sharia provisions. The purpose of this study is to analyze the service contracts of Islamic banks in the review of fiqh muamalah maliyah. The type of qualitative research used in this study describes descriptively to provide a clear picture of the implementation of the contract used in the service products provided by Islamic banking. The literature study in this study was carried out by collecting data in the form of journals, books, Fatwa DSN, KHES in order to strengthen the conclusions that were built. The results of this study describe the operational concepts of service contracts: wakalah, hawalah and kafalah in Islamic banking. Furthermore, the findings in this study reveal that service contracts in wakalah, hawalah and kafalah contracts that are applied to various products in Islamic banking are appropriate in the review of fiqh muamalah maliyah.